(untitled) (Journal of Pharmaceutical Negative Results, 2022)
Background- As of now prostatic carcinoma (PCa) is the second leading site of cancer among males in almost all the major Indian cities and is among the top ten leading sites of cancer in the rest of India. The diagnosis of PCa is not direct. It passes through various stages from clinical suspicion to biopsy diagnosis. The clinical symptoms usually lead to further investigations in the form of digital rectal examination (DRE), estimations of serum prostate specific antigen (PSA) levels. These investigations, although contributory, are not diagnostic of PCa. There was a need to study as to what levels of PSA actually imply the need for biopsy. This information becomes more practically relevant in Indian scenarios where economic constraints are always present for detailed investigations of biopsy and further workup. This will also cut down the number of such unnecessary biopsies done yearly. Every consecutive trus guided biopsy sent for histopathological examination to rule out malignancy was studied for its outcome and was correlated with age and the PSA levels.Methods-This is a retrospective study that includes all the consecutive TRUS-guided prostate biopsies sent to the department of pathology during a study period of one year. The inclusion criteria followed was that there was no previous diagnosis of PCa, suspicious cases on DRE, and or recorded PSA levels. The exclusion criteria followed was that the re-biopsy specimen, previously diagnosed cases of PCa, and biopsies which were not satisfactory for opinion. Following histopathological diagnosis, the data was studied for the association of age, PSA levels, and PCa, and results were tabulated.Results and Conclusion- In the Indian scenario, PSA levels of 11-50 ng/dl and levels above 100 ng/dl were highly associated with PCa in patients aged 60 years and above. PSA levels between 51-99 ng/dl had the least incidence of PCa irrespective of age. Carefully categorizing high-risk patients will reduce the unnecessary prostatic biopsies done and thereby reduce the economic as well as mental stress the patient undergoes through these procedures.